Mapping The Potential of Sports Faculties in Indonesia - Nugroho, Wisnu; Mulyawan, Rizki; Primasoni, Nawan; Salafi, Muhammad Irvan Eva; Nurfadhila, Risti; Hafidz, Sholeh; Mulyadi, Rekyan Woro Mulaksito (Jorpres (Jurnal Olahraga Prestasi), 2024)
So far there has been no study that has carried out mapping of study programs, facilities and infrastructure including laboratories and health services offered to the community. Judging from the literature review at all Sports Faculties in Indonesia, the aim of this research is to map the potential of sports faculties throughout Indonesia through study programs, laboratories and service facilities so that the potential of sports faculties is known. This research method involves collecting data from libraries and exploring research objects using various sources of library information, such as books, encyclopaedias, scientific journals, newspapers, magazines, and digital documents. The sample for this literature study consisted of 15 campuses that have sports faculties. Universitas Negeri Yogyakarta has the greatest number of sports study programmes among all campuses. UNM offers a sports faculty provided with appropriate and diverse related laboratories. There are five campuses, namely UPI, UNJA, UNIMA, UNDIKSHA, and UNCEN, which provide limited information about their laboratories. Currently, only UNESA, UM, and UNY have virtually identical quantitative measures. Surabaya and Yogyakarta State Universities own the majority of service facilities, while other sports campuses require new facilities to produce financial resources for universities and provide services to the public and academic community. Collaboration among sports institutions in Indonesia is necessary to cultivate proficient sports graduates across different locations. In addition to fostering healthy rivalry among sports faculties to promote their development, each campus should also seek suitable benchmarks based on their unique qualities, ensuring that each sports faculty have distinct advantages. There is a hope to establish sports universities in Indonesia as part of long-term planning.